Integrated approach for milling impeller parts. Issue 2 (4th March 2018) - Lin, Than; Premarathna, Aruna; Bohez, Erik L.J.
ABSTRACT: This paper presents an integrated approach for 4-axis milling impeller parts. Impeller blades are designed with a ruledsurface which is twisted to achieve the required performance. It can affect as an undercut or overcut on the part surface and collisions during machining. A method to manufacture impeller parts on a 4-axis machine is presented. Impeller 3D CAD models are implemented using geometric design parameters and CAM for 4axis Point Milling and Flank Milling are prepared under the SIEMENS UG NX. A postprocessor for desktop 4-axis CNC Mill using MATLAB® and a virtual machine tool simulator using VeriCUT® has been developed. Actual machining for impeller blades are done with Desktop 4-axis CNC Mill for the verification and validation purposes. GRAPHICAL ABSTRACT: